A new species of Rhinophis Hemprich, 1820 (Reptilia: Uropeltidae), from cloud forest of the Knuckles massif of Sri Lanka - Wickramasinghe, L.j. Mendis; Vidanapathirana, Dulan Ranga; Wickramasinghe, Nethu; Gower, David J. (Zootaxa, 2020)
A new species of uropeltid snake is described from the Knuckles Conservation Forest, Matale District, Sri Lanka. Rhinophis gunasekarai sp. nov. is superficially most similar to Rhinophis phillipsi in having yellow lines on the dorsum, blotches on the lateral body, and a relatively small tail shield, but it differs from that species in having substantially fewer ventrals, and a unique number and disposition of the dorsal yellow lines and lateral blotches. The new description brings the uropeltid fauna of Sri Lanka to 17 currently recognized species, all Rhinophis.